Combined effects of current-smoking and the aldehyde dehydrogenase 2*2 allele on the risk of myocardial infarction in Japanese patients. Issue 1 (5th January 2015) - Morita, Kazunori; Miyazaki, Hiroko; Saruwatari, Junji; Oniki, Kentaro; Kumagae, Naoki; Tanaka, Takahiro; Kajiwara, Ayami; Otake, Koji; Ogata, Yasuhiro; Arima, Yuichiro; Hokimoto, Seiji; Ogawa, Hisao; et al.
Highlights Aldehyde dehydrogenase 2 (ALDH2) detoxifies toxic aldehydes in cigarette smoke. Current-smoking ALDH2*2 allele carriers were at risk of myocardial infarction (MI). Current-smoking and ALDH2*2 synergistically increased the peak creatine kinase. Current-smoking and ALDH2*2 synergistically increased triglycerides in MI subjects.